English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Step by step please!

2007-07-08 11:00:32 · 3 answers · asked by zex_suik 2 in Science & Mathematics Mathematics

3 answers

Factor x^3 out of the equation 3x^5 - 5x^3 = 0. Then

x^3( 3x^2 - 5) = 0

For the expression to be 0 one of the factors has to be zero.

If 3x^2 -5 = 0, then x^2 = (5/3), or what is the same
x = sqrt(5/3) and x = -sqrt(5/3).

If x^3 = 0, then x = 0.

The roots of the equation are

x = 0 with multiplicity 3
x = sqrt(5/3) and
x = -sqrt(5/3).

2007-07-08 11:09:12 · answer #1 · answered by Bazz 4 · 1 0

3x^5-5x^3
=x^3(3x^2-5)
so x=0 or x=+-sq rt(5/3)

2007-07-08 11:08:01 · answer #2 · answered by MAHAANIM07 4 · 0 0

3x^5 - 5x^3 =

x^3 * (3x^2 - 5) =

now it' s easy ... continue

2007-07-08 11:06:58 · answer #3 · answered by oregfiu 7 · 0 0

fedest.com, questions and answers